Learning in Virtual Reality: Bridging the Motivation Gap by Adding Annotations - Vogt, Andrea; Albus, Patrick; Seufert, Tina (Frontiers in Psychology, 2021)
One challenge while learning scientific concepts is to select relevant information and to integrate different representations of the learning content into one coherent mental model. Virtual reality learning environments (VRLE) offer new possibilities to support learners and foster learning processes. Whether learning in VR is successful, however, depends to a large extent on the design of the VRLE and the learners themselves. Hence, adding supportive elements in VRLEs, such as annotations, might facilitate the learning process by guiding attention and supporting the selection of relevant information. Additionally, the mapping of pictorial and verbal information is eased by these annotations. The beneficial effect of annotations is highly dependent on learners’ intrinsic motivation as intrinsic motivation while learning also affects the information selection and visual search patterns. In our experimental study (N=61), we compared two conditions: learning in a VRLE with or without annotations. We measured the learning outcome on three different levels (knowledge, comprehension, and application). Additionally, we investigated intrinsic motivation as a moderator for the effect of annotations on learning outcome. We found no significant main effect of annotations on learning outcome. The moderating effect of intrinsic motivation for annotations on the overall learning outcome was significant. Our results imply that learners are either intrinsically motivated or need additional support by annotations as these support the selection of relevant information in the VRLE and therefore enable them to learn successfully. Which type of quantity of annotations supports learning processes best needs to be explored in future research.